Validation of Questionnaire to Assess the Impact of Dementia on the Family - Mafalda Sofia Gomes Oliveira da Silva; Luís Octávio de Sá; Sandra Sofia Barbosa Pinto de Almeida; Ana Catarina Rodrigues da Silva Reis (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To validate a questionnaire to assess the impact of dementia on one of the household members. Methods: Methodological study. The instrument was designed based on literature review, expert opinion, and researchers' experience and then applied to a non-probability convenience sample consisting of 262 family members who live daily with a person with dementia. The construct validity was studied by exploratory factor analysis, principal components method, with varimax rotation of the items. Results: An instrument with 30 items was obtained, distributed in four dimensions: "Emotional dimension," "Economic dimension," "Family relations dimension," and "Support-seeking dimension." Factor analysis revealed a total explained variance of 54.96% and a total Cronbach's alpha of .899. Conclusions: The instrument presents high internal consistency, grouped into four dimensions, all closely related to the family's adaptation to the onset of dementia in one of its members.